Yerevan’s transformation into a smart city: innovating infrastructure and driving sustainable urban development - Hovhannes YERITSYAN; Lusine SARGSYAN (Smart Cities and Regional Development Journal)
Objectives: The research explores how Yerevan is developing into a smart city, emphasising strategies for dealing with challenges including aging infrastructure, budgetary limitations, and equal access while encouraging sustainable urban growth.